A Methodology of Persona-centric Service Design - Hosono, S.; Hasegawa, M.; Hara, T.; Shimomura, Y.; Arai, T. (Cranfield University Press, 2009)
In order to clarify the customer’s inclination and provide them with better services, the persona-scenario method has been accepted in Requirements Engineering. A CAD tool proposed in Service Engineering also adopts persona-scenario and focuses on denoting and visualizing the quality factors in service receivers. However, the process of service development with persona has not been fully discussed yet. This paper proposes a methodology to identify the boundary of a whole service system with role and user personas, and formalize the procedure of service development with them. The methodology in service development is exemplified through e-learning services.
Organised by: Cranfield University
Keywords: User centric design; Requirements Engineering; Service Engineering; CAD